Effects of Dietary Gamma-Aminobutyric Acid (GABA) Inclusion on Acute Temperature Stress Responses in Juvenile Olive Flounder (Paralichthys olivaceus) - Abayomi Oladimeji Ogun; Haham Kim; Sooa Yoon; Suhyun Lee; Hyuncheol Jeon; Deni Aulia; Junhyeok Hur; Seunghyung Lee (Animals)
This study investigated the potential of dietary gamma-aminobutyric acid (GABA) inclusion to mitigate acute temperature stress impacting the physiological resilience of juvenile olive flounder (Paralichthys olivaceus). A total of 360 juvenile fish, with an average initial weight of 12.97 ± 0.1 g (mean ± SEM), were randomly assigned in triplicate to 18 tanks (20 fish per tank) and reared at 19.5 °C for 8 weeks, with bi-monthly collection of growth performance data. The fish were fed one of six experimental diets: control (GABA74), 174 ppm of GABA (GABA174), 275 ppm of GABA (GABA275), 396 ppm of GABA (GABA396), 476 ppm of GABA (GABA476), and 516 ppm of GABA (GABA516). At the end of the trial, one group of fish was subjected to lethal temperature stress (31 °C) for 48 h, while another was exposed to acute temperature stress (29 °C) for 6 h. Growth performance remained relatively stable across all inclusion levels (p > 0.05), with the final body weight (FBW) ranging from 48.2 ± 0.3 g (GABA174) to 50.3 ± 0.6 g (GABA516) and the feed conversion ratio (FCR) varying between 2.06 ± 0.07 (GABA396) and 2.35 ± 0.07 (control). There were no significant differences in average whole-body composition across all dietary treatments, with moisture content ranging from 74.8 to 75.0%, crude protein from 17.8 to 18.2%, crude lipid from 2.89 to 3.15%, and crude ash from 3.62 to 3.80%. Similarly, there were no significant differences in cumulative survival rates during lethal temperature exposure between the GABA-supplemented groups and the control group, with an average of 28.5 ± 4.6%. Additionally, GABA inclusion did not significantly alter plasma-free amino acid profiles, antioxidant enzyme activities, or immune functions (p > 0.05). However, temperature significantly reduced the levels of superoxide dismutase (SOD) from 3.34 ± 0.17 to 2.29 ± 0.36 µg/mL and increased the levels of glutamate oxaloacetate transaminase (GOT) from 17.1 ± 0.8 to 46.3 ± 6.2 U/L, glutamate pyruvate transaminase (GPT) from 14.4 ± 0.6 to 30.2 ± 2.1 U/L, glucose (GLU) from 13.3 ± 0.5 to 68.7 ± 7.7 mg/dL, total protein (TP) from 2.94 ± 0.00 to 3.21 ± 0.1 g/dL, and cortisol from 5001 ± 147 to 6395 ± 194 ng/mL. Furthermore, no significant changes were observed in the expression of key stress-related genes, including heat shock proteins (hsp60, hsp70, and hsp90) and the warm water acclimation-related gene wap65. This study establishes the safety of GABA as a dietary inclusion for olive flounder and highlights its potential to enhance stress resilience in aquaculture. However, the effectiveness of GABA-based interventions could depend on critical factors such as dosage, stress duration, and species-specific responses. Our findings highlight the need for further research to optimize GABA inclusion strategies, particularly with consideration for long-term physiological impacts.